2022
DOI: 10.3390/molecules27020530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phenolic Metabolites in Purified Extracts of Three Wild-Growing Herniaria L. Species and Their Antioxidant and Anti-Inflammatory Activities In Vitro

Abstract: The work is aimed at phytochemical characterization and In Vitro evaluation of antioxidant actions, anti-inflammatory effects, and cytotoxicity of purified extracts from three rupturewort (Herniaria L.) species, i.e., Herniaria glabra (HG), H. polygama (HP), and H. incana herb (HIh). The total phenolic content established in the purified extracts (PEs) of HIh, HP, and HG was 29.6, 24.0, and 13.0%, respectively. Thirty-eight non-saponin metabolites were identified using LC-HR-QTOF-ESI-MS; however, only 9 were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…This compound was identified as Licoagroside B, although it was not previously identified in carrot. However, the fragment spectra match those in the PubChem database and in the literature [63,64]. Chevalier et al [65] also reported this compound as a discriminating factor for carrot varieties; however, the authors reported only the molecular formula without further identification.…”
Section: Identification Of Important Ionssupporting
confidence: 64%
“…This compound was identified as Licoagroside B, although it was not previously identified in carrot. However, the fragment spectra match those in the PubChem database and in the literature [63,64]. Chevalier et al [65] also reported this compound as a discriminating factor for carrot varieties; however, the authors reported only the molecular formula without further identification.…”
Section: Identification Of Important Ionssupporting
confidence: 64%
“…In general, the positive therapeutic effects of Herniaria in this study are consistent with previous reports that documented the medicinal use of the genus Herniaria as antispasmodic, antihypertensive, lithophytic, and diuretic agents. They demonstrated antioxidant and antimicrobial activities, as well [ 14 ]. Additionally, similar results were observed from several polyphenolic-rich extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Herniaria hemistemon J.Gay is an herb native to North Africa and Asia, spanning from Morocco to Iran and the Arabian Peninsula but currently introduced to other parts of the world. The plant has been traditionally used in the management of hernia [ 12 , 14 ]. It has also shown remarkable biological activities including antioxidant [ 15 , 16 ], antimicrobial [ 16 ], and in vitro antischistosomal [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of special phytochemicals to develop novel anti-oxidative, mitochondrial protection, and anti-apoptotic drugs on DA neurons may achieve the purpose of treating or curing PD. Narcissoside (NCS) ( Figure 1 ) is isolated from Sambucus nigra flowers (elderflowers), and has been reported to have several pharmacological activities, such as antioxidant [ 23 , 24 ], anti-inflammatory activities [ 25 ], anti-SARS-CoV-2 [ 26 ], antihypertensive properties [ 27 ], and antitumor potential [ 28 , 29 ]. It also activates TRPV1 channels in dorsal root ganglion sensory neurons linked with pain-accompanied itch [ 30 ].…”
Section: Introductionmentioning
confidence: 99%